Dampak Dana Alokasi Umum (DAU) Terhadap Kemiskinan Di Kota Tangerang - Imal Istimal (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2012)
The objectives of the study are to: (1) analyze the correlation between DALI and poverty and (2) the effect of DALI to poverty in Kota Tangerang. The values examined in this study used regression and correlation method. The result of the study show that (1) DALI and poverty has negative correlation, is -0,248 which stated that between DALI and poverty has low correlation in di Kota Tangerang. (2) Estimation result by regression showed that the coefficient of DALI is negative to poverty by -3.9 percent. This value stated that every changes one unit of DALI (in rupiah) would reduce poverty by 3.9 percent.